Politics and Power - Kidd, Warrern; Legge, Karen and Harari, Philippe (New York Palgrave Macmillan, 2010)
"Politics and Power offers a lively and up-to-date overview of classic and contemporary debates in an important sub-area of the discipline. As with other titles in the series, it provides both a careful blend of theory, evidence and examples and a stimulating array of exercises and activities for the student to apply and reinforce their understanding. Covering issues and debates ranging from theories of power, the state and nationalism to voting patterns, political ideologies, and the role of direct action in political processes, it is an ideal starting-point for any student wishing to gain a strong basic grounding in political sociology"--Provided by publisher.
Include Reference and Index
Keywords: Political sociology -- Power (Social sciences) -- Sociology--Study and teaching (Secondary)